The Effect Of Good Corporate Governance (Gcg), Profitability And Leverage On Earnings Management In Mining Companies - citradika, didha putri; Iliana, Vilka (REVENUE: Jurnal Manajemen Bisnis Islam, 2025)
This study is a causality research that aims to analyze the influence of GCG, profitability and leverage on Earnings Management. GCG variables are measured using Independent Commissioners and Audit Committees. Profitability is measured using Retrun On Assets (ROA). Leverage is measured using the Debt To Asset Ratio (DAR). Meanwhile, the Profit Management variable is measured using the Discretionary Accrual model. This research is a quantitative research. The source of data for this research is secondary data in the form of company financial statements obtained from the Indonesia Stock Exchange (IDX) website. The analysis methods used include descriptive statistical tests, classical assumption tests (multicoloniality tests, autocorrelation tests, heteroscedasticity tests, normality tests), and hypothesis tests. Based on the results of data analysis, the results of the study partially show that GCG has a positive and insignificant effect on Earnings Management. Profitability has a positive and significant effect on Profit Management. Meanwhile, Leverage has a negative and significant effect on Earnings Management.